Changes in conditions, practices, and relationships between teachers and students in rural Mexican high schools during the COVID-19 pandemic - Guzmán Gómez, Carlota (2022)
This article analyzes some of the changes that occurred in Mexican community distance-learning high schools during the COVID-19 pandemic, particularly regarding the conditions of actors within school systems, the new activities associated with distance-learning, and teacher-student relationships. From the perspective of interpretive sociology and through semi-structured interviews, the aim is to take the perspective of head teachers and teachers into account, to show their role in the transformation of the schools. It was found that, even though the pre-existing problems of head teachers and teachers were exacerbated, these actors played a leading role and carried out this teaching work with creativity and commitment